Development scenarios for the taxi services market in Vietnam in terms of competitiveness - Hong, Pham Thi Thanh; Thuy, Nguyen Thi Thu (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
The study objective was scenario forecasting of growth prospects of the service operators market on the example of Vietnam. The study is based on the results of a survey of 231 Hanoi residents who use traditional taxi service and app-based taxi service (TTS&ABTS). Using an integrated model, the quality of taxi services (TS) was assessed based on the satisfaction level with the individual components of the services provided. The perception features of TTS&ABTS in the context of different categories of respondents have been revealed. Using IPA-analysis, the competitiveness of the taxi operators in the country has been determined. Considering the impact of external factors that create risks and opportunities for the development of TS, economic scenarios for the development of TTS&ABTS have been simulated. The results can be useful in legislative regulation of the taxi market (TM) in Vietnam and the development of effective marketing strategies by taxi operators.